Causes of death in HIV-1-infected patients treated with antiretroviral therapy, 1996-2006: collaborative analysis of 13 HIV cohort studies. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2010)
We examined specific causes of mortality in human immunodeficiency virus type 1 (HIV-1)-infected patients who initiated antiretroviral therapy (ART) in Europe and North America from 1996 through 2006, and we quantified associations of prognostic factors with cause-specific mortality.
Keywords: Adolescent; Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Cause of Death; Cohort Studies; Europe; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; North America; Prognosis; Retrospective Studies; Risk Factors; Young Adult